PEMBUATAN PLASTIK POLIHIDROKSI YANG DAPAT TERDEGRADASI DARI SINGKONG GAJAH (Manihot esculenta) DENGAN PENAMBAHAN GLISEROL SEBAGAI PLASTICIZER - Syafriyanti, Yuly; Gunawan, Rahmat; Saleh, Chairul (Jurusan Kimia FMIPA UNMUL, 2016)
The synthesis of plastic production which can be degreded use manihot esculenta extract already researched. The method of this research using blending according to physics with the addition of glycerol as a plasticizer and FT-IR characterization. The result show that the glycerol concentrate that produce plastics which is easy to degreded well, exist in 45% concentrate whit a value of 25% water resistance and degradability value of 19,7 mg/day. The date of FT-IR give information that there are group alteration or between before and after glycerol increasing in long wave intensity